Teori Dan Implementasi Pengambilan Keputusan Dan Kaitannya Dengan Teori Rational Choice Dalam Administrasi Publik - Angye Mareta Y; Fachri Adnan; Afriva Khaidir (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to analyze the theory and implementation of decision-making in public administration and to examine its relation to Rational Choice Theory. In the context of public administration, decision-making is influenced not only by norms and bureaucratic structures but also by the rationality of the actors involved. Rational Choice Theory views individuals as rational agents who make decisions based on cost-benefit calculations to maximize personal interest. This study adopts a qualitative approach using literature review and content analysis methods on public policies and relevant case studies. The findings reveal that the implementation of decision-making in the public sector is often not entirely rational due to the influence of political, social, and cultural factors. Nevertheless, elements of Rational Choice Theory remain an important framework for understanding the motivations of bureaucratic actors in formulating and executing policies. This study recommends integrating rational approaches with normative and contextual perspectives in public administration practices to produce more effective and responsive decisions.